Mathematical knowledge of elementary education student teachers: variable analysis - Segarra, Jaime; Julià, Carmen (Uniciencia, 2021)
The paper studies the knowledge elementary school student teachers have regarding numbers and geometry. This research study is quantitative and used descriptive and inferential statistical techniques. A total of 20 released questions were selected from the TIMSS test and applied to 97 first-year students in an Elementary Education program. Results were presented in two different sections. The first section shows that those who come from a Bachelor's Degree in Science and have received mathematics in the last two years obtained higher scores (p < 0.05). The second section indicates that students obtain higher scores in the number content domain and the knowing cognitive domain (p < 0.05). The study will strengthen the weaknesses presented by the groups of students when redesigning the Teaching and Learning Mathematics course.